Ecotoxicological Study of Insecticide Effects on Arthropods in Common Bean. Issue 1 (19th February 2015) - de Barros, Emerson Cristi; Ventura, Hudson Vaner; Gontijo, Pablo Costa; Pereira, Renata Ramos; Picanço, Marcelo Coutinho
Abstract : Arthropods are an important group of macroorganisms that work to maintain ecosystem health. Despite the agricultural benefits of chemical control against arthropod pests, insecticides can cause environmental damage. We examined the effects of one and two applications of the insecticides chlorfenapyr (0.18 liters a.i. ha-1) and methamidophos (0.45 liters a.i. ha-1), both independently and in combination, on arthropods in plots of common bean. The experiment was repeated for two growing seasons. Principal response curve, richness estimator, and Shannon–Wiener diversity index analyses were performed. The insecticides generally affected the frequency, richness, diversity, and relative abundance of the arthropods. In addition, the arthropods did not experience recovery after the insecticide applications. The results suggest that the insecticide impacts were sufficiently drastic to eliminate many taxa from the studied common bean plots.